PENGARUH SUBJECTIVE NORM DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP INTENTION TO COMMIT DIGITAL PIRACY - Ruslim, Tommy Setiawan; Rahardjo, Mukti; Widjaya, Hannes (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
In the era of computerization today, almost every company big and small usecomputers in running its business activities. Even not only within the scope of the company, both of the students, other businessmen are also many who use computers to help business activities. The high level of demand for the needs of the software to create a number of parties to create pirated software with a much cheaper price, so it is allegedly can make software makers experience losses of course. By doing a similar research as conducted by YoonÂ (2011), the authors conducted research on the intention to perform digital piracy in S1 Management Faculty of Economics Tarumanagara University. By using questionnaires, data is processed with PASW 18.00 software, there is also result of this research is subjective norm as independent variable (X1) and perceived behavioral control (X2) have significant influence to intention to commit digital piracy (Y).